Trucking costs and overcosts in Africa - (:unkn) unknown (My University, 1990)
Why is trucking so expensive in Africa? In order to answer this question, we must compare the structure of African costs with those of other countries. The method developed to this end allows to separate the influence of the different factors and, in particular, the effect of input prices from the productivity effect. The weak productivity of African vehicles results both from the high kilometric consumptions, and the small yearly number of kilometers travelled, as well from the high empty return rate.
Keywords: African Research